Drifter trajectories North Sea July 2019 - Jens Meyerjürgens; Thomas Henry Badewien; Oliver Zielinski; Lukas Ross; Claudia Thölen; Jana D Schmitz; Axel Braun (PANGAEA, 2021)
Drifter position data from drifter deployments in July 2019 im the German Bight. The drifters were deployed from RV Alkor. The drifter position was send every 10 minutes via the Globalstar satellite transmission service. The drifters were 0.5 m in height with a subsurface drogue which is directly to the housing. The drag area ration of the deployed configuration is R=25.6.